Cheese and Whey - Moatsou, Golfo; Moschopoulou, Ekaterini (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cheese is an excellent and complex food matrix that preserves in concentrated form valuable milk constituents, such as proteins, minerals, vitamins, and biofunctional lipids. The formation of cheese mass requires the removal of whey, i.e., water and soluble milk substances-proteins, minerals, lactose, and vitamins. It is well known that whey, apart from being a serious environmental threat, is a valuable substrate for the formation of new products with excellent functional and biological activities. This reprint aims to share research related to (i) cheese production, ripening, and properties, and (ii) whey and whey components' functionality and biological value, as well as whey exploitation and processing.